Administrative Law Approaches to Corruption Control: A Systematic Literature Review on Strategies in Developing and Developed Countries - Riyan Israyudin; Laode Rudita (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Corruption remains a persistent challenge worldwide, manifesting differently in developing and developed countries. While developing nations struggle with systemic corruption due to weak institutional frameworks and limited administrative oversight, developed countries face more sophisticated forms, such as regulatory capture and lobbying. This study systematically reviews administrative law approaches to corruption control, comparing strategies across different governance contexts. Using a Systematic Literature Review (SLR) guided by the PRISMA framework, this research analyzes existing literature to identify key administrative mechanisms for mitigating corruption. The findings highlight that developing countries require stronger regulatory enforcement and institutional reforms, while developed nations must enhance transparency in policymaking and lobbying regulations. Additionally, international cooperation and emerging technologies are crucial in addressing corruption globally. The study concludes that effective anti-corruption strategies must be adaptable to contextual administrative and legal challenges. The insights provided contribute to refining administrative law policies aimed at fostering accountability and integrity in governance.